Determinants of capital structure: Evidence from UK listed firm panel data - Wang, Zicong (2012)
This paper follows many previous empirical researches, identifying and finding the determinants of capital structure of UK-listed firms. It chooses indicators for each explanatory variable and apply regression model to obtain the qualitative results, and then analyse them. Each research always gets its own results. This paper tends to find its results in the recent years and compare it with previous paper. 200 UK-listed companies in the period of 2001 to 2011 are investigated. Capital structure of a firm is computed in two ways, long-term debt ratio and short-term debt ratio. An OLS regression is used. The results observed show that growth opportunities variable is the most significant determinant of capital structure, followed be volatility and uniqueness. Profitability, size, non-debt tax shields and tangibility are not significant in all the models. Key words: capital structure; leverage; firm characteristics.